Violencia verbal y comportamiento negativista desafiante, en niños de 7 a 12 años de la Ciudadela Brisas del Rio de la ciudad de Babahoyo - Alvarado Macías, Lucas Alfredo (2018)
The current research, with a study problem, aims to show how verbal violence interferes with the integral development of infants and in consequence behavioral disorders such as defiant negativist behaviors develop, situation that occurs in infants; within the home sphere, behavior that is important for the scope of this study. And check if the behavioral problems of the children, of the Brisas del Rio community, are the result of verbal violence. The theoretical framework was deployed with the following topics: verbal violence, defiant negative behavior and other contexts no less interesting but very relative for the development of the child. In the methodological part the information was collected by means of the Inductive method for intuition and verification of the collected data about the subject and Deductive to conclude the types of behavior obtained by children inflicted by verbal violence starting from what is known up to what is unknown. For the progress of this study, he had a maximum population, with the due and informed approval of his parents. The findings of this study is the attitude of the parents and their contribution to the home context environment; they contribute to the integral formation of the child, and their respective behaviors assist in their social action and such indicated behavior is numerously influenced by the environment and learned, and these adaptive behaviors generate concern since it represents disintegrative difficulties in the development and social relations interpersonal and personal of the infant as it is, defiant negativistic behavior.